Effects of Seed Priming on Germinability and Biochemical Parameters of Praecitrullus Fistulosus (Stocks) Pangalo (Bangladesh Journal of Botany, 2024)
The physiological dormancy of freshly harvested seeds of Praecitrullus fistulosus naturally overcomes to some extent if the seeds are stored before germination. Therefore, to avoid storage period, the priming treatments viz., GA3 (150, 500, 1000 µg/ml), cytokinin (150, 500, 1000 µg/ml Kn), ethylene (150, 500,1000 µl/l ethrel), KNO3 (150, 500 µg/ml), HNO3 (150, 500µl/l), and water (hydropriming) were tested at 250C at intervals of 12 and 24 hours, respectively. Conventional seed priming can provide unpredictable outcomes for morpho-physiological characters, as what works for one species or variety may not be successful for another. As a result, it is necessary to investigate the metabolic components that affect seed physiology and germination. Therefore, in the present study, seed metabolic efficiency (SME) and various biochemical parameters were observed, such as total soluble sugars, total starch, total soluble protein, total free amino acids, and α-amylase content. It was observed that seeds primed with 500 µgml-1 KNO3 for 12 h and 24 h respectively, recorded maximum seed metabolic efficiency. Priming in GA3 and KNO3 showed significant improvement in the biochemical parameters which was manifested in better seed metabolic efficiency. Further, correlation analysis validated that SME exhibited a significant positive correlation with the content of total soluble sugar, total free amino acids, and α- amylase activity and negatively correlated with total starch and total soluble protein content. With appropriate priming treatments, it is possible to improve germinability, seed metabolic efficiency, and biochemical attributes of freshly harvested seed lots. This finding suggests that implementing these correlations could potentially alleviate dormancy states in related species within the same family.Bangladesh J. Bot. 53(2): 217-225, 2024 (June)